Antimicrobial Activity Enhancers: Towards Smart Delivery of Antimicrobial Agents - Mariusz Skwarczynski; Sahra Bashiri; Ye Yuan; Zyta M. Ziora; Osama Nabil; Keita Masuda; Mattaka Khongkow; Natchanon Rimsueb; Horacio Cabral; Uracha Ruktanonchai; Mark A. T. Blaskovich; Istvan Toth (MDPI AG, 2022)
The development of effective treatments against infectious diseases is an extensive and ongoing process due to the rapid adaptation of bacteria to antibiotic-based therapies. However, appropriately designed activity enhancers, including antibiotic delivery systems, can increase the effectiveness of current antibiotics, overcoming antimicrobial resistance and decreasing the chance of contributing to further bacterial resistance. The activity/delivery enhancers improve drug absorption, allow targeted antibiotic delivery, improve their tissue and biofilm penetration and reduce side effects. This review provides insights into various antibiotic activity enhancers, including polymer, lipid, and silver-based systems, designed to reduce the adverse effects of antibiotics and improve formulation stability and efficacy against multidrug-resistant bacteria.